Electromagnetic wave propagation on a thin wire above earth. - Olsen, R.G (IEEE Transactions on antennas and propagation)
The electromagnetic properties of a current on a thin horizontal wire above a flat lossy earth is reviewed. Attention is given to the historical development of the topic, starting with the seminal work of Carson. Particularly, the importance of Professor Wait's contribution to the initial understanding of the modal and radiative behaviors of the current, as described in his influential paper (see Radio Sci., vol.7, p.675, 1972), is discussed in detail. A description of Wait's full wave analysis is provided to show how that analysis justified many of the assumptions embedded in Carson's result and how that same analysis later led to a fuller understanding of the current's spatial spectrum. Although no rigorous proof is known to exist with respect to the completeness of this spectrum, a necessary condition for completeness is offered; the basis of this condition is the measurable input conductance of the wire. The paper concludes with a short discussion on the various extensions of Wait's classic work that have been provided over the last two decades